Differences in academic stress and stress coping style by characteristics of nursing undergraduates - Yahaya Jafaru; Esther Kikelomo Afolabi; Monisola Yetunde Jane Omishakin (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: The need to act against stress required effective coping strategies for students to cope with academic activities. However, the degree of stress and type of coping style differ between nursing students; and assessing the nursing program’s level of stress for intervention planning is recommended to nurse educators.Purpose: To examine the differences in academic stress and stress coping style by characteristics of nursing undergraduates.Method: The descriptive study adopted a cross-sectional design with undergraduate nursing students as the population of the study. Census sampling was used, and the academic stress inventory and the stress coping style inventory were the instruments for data collection. The results were presented in means and standard deviations, and ANOVA was used for inferential analysis.Results: There was a significant difference in peer stress across the age brackets, (p = 0.004). The male respondents have lower mean academic stress than female respondents except for peer stress. There was a significant difference between the mean academic stress between the two genders in teacher stress and peer stress, p = 0.02 and 0.04 respectively. The mean academic stress is higher at 300 and 400 levels except in studying in groups stress. Active problem coping is having the highest mean score across all age brackets. There is no significant difference in stress coping style across all the factors. Male respondents have higher mean stress coping style than female respondents in active emotional coping and active problem coping with a significant difference, p = 0.011 and 0.045 respectively. The 500-level respondents have the highest mean stress coping style across all the factors than respondents from other levels.Conclusion: In planning interventions against academic stress for undergraduate nursing students, preference for test stress should be given to lower age brackets. Female students require more attention than male students. The 300 and 400-level students should be considered more than the other levels. Moreover, different methods of coping, where to apply them and the consequences of each should be taught to students irrespective of their age, gender, or level of study.